Positive solutions for a Hadamard-type fractional-order three-point boundary value problem on the half-line - Xu, Jiafa; Cui, Yujun; O’Regan, Donal (Nonlinear Analysis: Modelling and Control, 2025)
In this paper, we study a Hadamard-type fractional-order three-point boundary value problem on the half-line. Under some growth conditions concerning the spectral radius of the relevant linear operator, the existence and multiplicity of positive solutions is obtained using a fixed-point method. Our results improve and generalize some results in the literature.